Tofacitinib - Nilgün Şentürk (Turkderm Turkish Archives of Dermatology and Venereology, 2022)
Tofacitinib is an oral inhibitor of janus kinases, which is approved for the treatment of rheumatoid arthritis, psoriatic arthritis, and ulcerative colitis in adults; its efficacy in the treatment of psoriasis has also been demonstrated in clinical studies. A 10 mg daily dose has been observed to achieve a PASI75 response in 40-64% of the patients with moderate to severe psoriasis at week 12 or 16. It provides advantage in the treatment of psoriasis due to oral use, lower cost compared to other biologics, and absence of organ toxicity.